Efficacy of Miltefosine for the Treatment of American Cutaneous Leishmaniasis (2010)
ABSTRACT: Miltefosine is an oral agent used for cutaneous leishmaniasis treatment. An open-label, randomized, phase III clinical trial was carried out in the Colombian army population. Miltefosine, 50 mg capsule was taken orally three times per day for 28 days (N = 145) or meglumine antimoniate, 20 mg/kg body weight per day for 20 days by intramuscular injection (N = 143). The efficacy of miltefosine by protocol was 69.8% (85/122 patients) and 58.6% (85/145 patients) by intention to treat. For meglumine antimoniate, the efficacy by protocol was 85.1% (103/121 patients) and 72% (103/143 patients) by intention to treat. No association was found between drug efficacy and L. ( V.) braziliensis or L. ( V.) panamensis species of Leishmania responsible for infection. Adverse gastrointestinal events were associated with the use of miltefosine, the meglumine antimoniate treatment was associated with adverse effects on the skeletal musculature, fever, cephalea, and higher toxicity in kidney, liver, pancreas, and hematological system.